Women on the Margins: A Case Study on The National Federation of Peasant Women in the Philippines (AMIHAN) - Arnedo, Francesca Therese A. (Animo Repository, 2021)
Throughout the years, the agricultural sector continues to face challenges such as land entitlement, unequal wages, and human rights violations. Along with these are gender- based issues that further intensify the difficulties faced by farmers, particularly peasant women. With the establishment of organizations like The National Federation of Peasant Women in the Philippines (AMIHAN), these challenges are given attention as it aids in upholding rights and providing voices for peasant women. This study explored the motivations behind AMIHAN’s establishment, its nature and how it differs from other women’s organizations, and how the organization amplifies voices and provides alternative platforms to peasant women in the Philippines. Two leaders and five peasant women were interviewed via the online conferencing platforms, Zoom and Messenger. Three main findings were inferred: 1) peasant women are united and empowered by the organization’s advocacies, 2) peasant women face both sector-specific and non-sector-specific issues, and 3) peasant women are given a platform to voice their issues through the organization. With the help of AMIHAN, the gap left out by the broad goals of women’s movements are addressed, and the inequality and oppression faced by peasant women are tackled.